2007
DOI: 10.1039/b6rp90031c
|View full text |Cite
|
Sign up to set email alerts
|

A rubric to characterize inquiry in the undergraduate chemistry laboratory

Abstract: Consensus does not exist among chemists as to the essential characteristics of inquiry in the undergraduate laboratory. A rubric developed for elementary and secondary science classrooms to distinguish among levels of inquiry was modified for the undergraduate chemistry laboratory. Both peer-reviewed experiments in the literature and commercially available experiments were evaluated using the rubric, revealing a diversity of uses for the word inquiry.The modified rubric provides a valid and reliable standard o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 21 publications
1
118
0
2
Order By: Relevance
“…Inquiry learning model is recommended for learning through invention. Guided inquiry is one of the various inquiry learning models which mainly consists of five steps, namely observation, manipulation, generalization, verification and application (Vishnumolakala, Southam, Treagust, Mocerino, & Qureshi, 2017;Fay, Grove, Towns, & Bretz, 2007;MartinHansen, 2002). Guided inquiry provides guidance in formulating investigative questions and/or other phases if required commonly for learners whose inquiry skill has not committed or established (Banchi, H., Bell, 2008;Wenning & Khan, 2011;Shen, 2007;Kuhlthau, 2010;Dounas-Frazer & Reinholz, 2015;Vishnumolakala et al, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Inquiry learning model is recommended for learning through invention. Guided inquiry is one of the various inquiry learning models which mainly consists of five steps, namely observation, manipulation, generalization, verification and application (Vishnumolakala, Southam, Treagust, Mocerino, & Qureshi, 2017;Fay, Grove, Towns, & Bretz, 2007;MartinHansen, 2002). Guided inquiry provides guidance in formulating investigative questions and/or other phases if required commonly for learners whose inquiry skill has not committed or established (Banchi, H., Bell, 2008;Wenning & Khan, 2011;Shen, 2007;Kuhlthau, 2010;Dounas-Frazer & Reinholz, 2015;Vishnumolakala et al, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…To simplify the matter, it is suggested that there should be four (4) levels of openness, namely Levels 0-3, and three categories of element to be incorporated into the laboratory manual, namely problem, ways and means and answers. The scientific enquiry rubric, as given by Fay et al (2007) for the levels of openness are summarized and described as in Table 2 below by the University of New South Wales, Australia (UNSW, 2017). The problem, procedure and methods for achieving solutions are provided to the student.…”
Section: Level Of Opennessmentioning
confidence: 99%
“…The student chooses the problem to explore, develops a procedure for investigating the problem, decides what data to gather, and interprets the data in order to propose viable solutions Source: Fay et al (2007) …”
mentioning
confidence: 99%
“…University students can't explain the observation outcomes in the laboratory and be less able to rationalize it 2 . Some researchers conduct the performance instrument development in the chemical laboratory, generally by the instrument design process, content validation and revision outcome instrument trial 3,4,1,5,6 . The result is that the developed performance assessment instruments have very good validity and reliability, meaning that the instruments developed can assess the students' laboratory skill correctly.…”
Section: Introductionmentioning
confidence: 99%